Surgical Management of Ipsilateral Internal Carotid Artery Stenosis and Unruptured Intracranial Aneurysm: Case Review and Treatment Considerations - Gautam, Diwas; Findlay, Matthew C.; Cole, Kyril L.; Couldwell, William T.; Rennert, Robert C. (Journal of Neurological Surgery Reports, 2024)
Introduction The coexistence of carotid artery stenosis and a concomitant downstream ipsilateral unruptured intracranial aneurysm requires unique treatment considerations to balance the risk of thromboembolic complications from carotid artery stenosis and the risk of subarachnoid hemorrhage from intracranial aneurysm rupture. These considerations include the selection of optimal treatment modalities, the order and timing of interventions, and potential management of antiplatelet agents with endovascular approaches. We present strategies to optimize treatment in such a case.Case Report We discuss the case of a 69-year-old woman with 90% stenosis of the right internal carotid artery and an ipsilateral, wide-necked, 4.8-mm, irregular-appearing right A1–2 junction aneurysm with an associated daughter sac. Open, endovascular, and mixed treatment strategies were considered. The patient selected and underwent a staged, open treatment approach with a carotid endarterectomy followed by a right craniotomy for microsurgical clipping of the aneurysm 5 days later. Both procedures were performed on daily full-dose aspirin without complications. On follow-up, the right carotid artery was widely patent, the aneurysm was secured, and the patient remained at her neurologic baseline.Discussion The presented strategy for ipsilateral carotid artery stenosis and an unruptured intracranial aneurysm initially optimized cerebral perfusion to mitigate ischemic risks while permitting timely aneurysm intervention without a need for dual antiplatelet therapy or to traverse an earlier procedure site.
Keywords: carotid artery stenosis; intracranial aneurysm; staged treatment; carotid endarterectomy; microsurgical clipping